Isoliquiritin promote angiogenesis by recruiting macrophages to improve the healing of zebrafish wounds. Issue 100 (May 2020) - Liu, Yu-Yang; Wu, Jia-Qi; Fan, Ruo-Yue; He, Zhi-Heng; Li, Chong-Yong; He, Ming-Fang
Abstract: Licorice is a widely used herbal medicine for the treatment of various diseases in southern Europe and parts of Asia. It has been reported that the isoliquiritin (ISL) from Glycyrrhiza root has the activity of promoting angiogenesis. The purpose of this study was to investigate the effect of ISL on the wound healing activity of zebrafish and its mechanism. 6-month-old zebrafish were injured in the skin (2 mm in diameter) and then treated with ISL. By measuring wound size and by histological examination, we found that ISL improved wound healing. In addition, 4-day-old zebrafish embryos of double transgenic line [Tg( fli-1 :EGFP)]/[Tg( mpeg: mCherry)] were suffered from tissue traumas and then treated with ISL. Through fluorescent microscopy, we found that ISL promoted macrophage recruitment and angiogenesis in the wound area. Through qPCR analysis, we found that ISL up-regulated the expression of genes related to inflammation and angiogenesis in zebrafish embryos. These results showed that ISL could promote inflammatory response and angiogenesis, which played key roles in promoting wound healing. Therefore, ISL can be used as a promising candidate to promote wound healing. Highlights: Isoliquiritin promoted the wound healing in the adult zebrafish skin. Isoliquiritin promoted the wound angiogenesis in the zebrafish embryos by macrophage recruitment. Angiogenesis and inflammation related genes were stimulated by ISL during wound healing.